ChemInform Abstract: Synthesis of N1 and N2 Coumarin Substituted 1, 2, 3‐Triazole Isomers via Click Chemistry Approach. Issue 31 (14th July 2016) - Shamala, Devadas; Shivashankar, Kalegowda; Chandra, Kalegowda; Mahendra, Madegowda
Abstract: from terminal alkynes, sodium azide, and bromomethylcoumarins